Meningkatkan Resiliensi keluarga dengan Leprosi melalui Mitigasi dan Adaptasi terhadap Wabah Covid - Tri Novita Irawati; Arifin Nurbudiono; Syaifur Rahman (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2023)
This activity aims to improve the quality of life of families who have had leprosy through adaptation and mitigation of the covid 19 outbreak. It was carried out by PerMaTa management in East Java Province which focused on 7 districts/cities, namely; Surabaya, Lamongan, Jember, Mojokerto, Blitar, Kediri and Ngawi. This activity is carried out through several stages, namely the preparation, implementation, and evaluation stages. In real terms, this activity takes the form of: (1) Economic Empowerment and Supervision in the form of capital assistance (2) Providing self-care materials in the form of providing self-care materials as an effort to prevent transmission of covid 19 (3) Providing school materials to children of persons affected by leprosy, activities this helps to ease the burden on parents of students in meeting the needs of school supplies and (4) Food Aid in the form of activities providing food assistance. The distribution of aid had problems because there was a policy of Large-Scale Social Restrictions (PSBB) on both the micro and macro scale, making the implementation of activities unable to run according to the timeline, but all programs were implemented properly and received a positive response from the community. Keywords: Impact of Covid 19, Leprosy, Family Resilience